Stillbirth: Perceptions among hospital staff in the Middle East and the UK. (October 2019) - Mohan, Suruchi; Gray, Thomas; Li, Weiguang; Alloub, Mohamed; Farkas, Andrew; Lindow, Stephen; Farrell, Tom
Abstract: Objectives Stillbirth is an important and yet relatively unacknowledged public health concern in many parts of the world. Public awareness of stillbirth and its potentially modifiable risk factors is a prerequisite to planning prevention measures. Cultural and regional differences may play an important role in awareness and attitudes to stillbirth prevention. The objective of this study was to evaluate and compare the awareness of stillbirth among hospital staff in Qatar and the UK, representing two culturally different regions. Study design An online population survey for anonymous completion was sent to the hospital email accounts of all grades of staff (clinical and non-clinical) at two hospitals in Qatar and one tertiary hospital Trust in the UK. The survey was used to gather information on the participants' demographic background, the experience of stillbirth, knowledge of stillbirth, awareness of information and support sources, as well as attitude towards investigation and litigation. Data were analysed using descriptive and comparative statistics (Chi-Square test and Fisher's exact test). Results 1002 respondents completed the survey, including 349 in the Qatar group and 653 in the UK group. There were significant differences in group demographics in terms of language, religion, gender, nationality and experience of stillbirth. The groups also differed significantly in the knowledge of stillbirth, its incidence and risk factors. The two groups took different views on apportioning blame on healthcare services in cases of stillbirth. The Qatar group showed significantly less awareness of available support organisations and relied significantly more on online sources of information for stillbirths (p < 0.001). Conclusions This comparative study demonstrated significant differences between the two culturally distinct regions in the awareness, knowledge and attitudes towards stillbirths. The complex cultural and other factors that may be contributory should be further studied. The results highlight the need for increasing public awareness around stillbirth as part of effective prevention strategies.